Dapoxetine, a Selective Serotonin Reuptake Inhibitor, Suppresses Zika Virus Infection In Vitro - Bingzhi Zhang; Jianchen Yu; Ge Zhu; Yun Huang; Kexin Zhang; Xuhan Xiao; Wenxuan He; Jie Yuan; Xiaoxia Gao (Molecules, 2023)
Zika virus (ZIKV) belongs to the Flavivirus genus of the Flaviviridae family, and is a pathogen posing a significant threat to human health. Currently, there is a lack of internationally approved antiviral drugs for the treatment of ZIKV infection, and symptomatic management remains the primary clinical approach. Consequently, the exploration of safe and effective anti-ZIKV drugs has emerged as a paramount imperative in ZIKV control efforts. In this study, we performed a screening of a compound library consisting of 1789 FDA-approved drugs to identify potential agents with anti-ZIKV activity. We have identified dapoxetine, an orally administered selective serotonin reuptake inhibitor (SSRI) commonly employed for the clinical management of premature ejaculation (PE), as a potential inhibitor of ZIKV RNA-dependent RNA polymerase (RdRp). Consequently, we conducted surface plasmon resonance (SPR) analysis to validate the specific binding of dapoxetine to ZIKV RdRp, and further evaluated its inhibitory effect on ZIKV RdRp synthesis using the ZIKV Gluc reporter gene assay. Furthermore, we substantiated the efficacy of dapoxetine in suppressing intracellular replication of ZIKV, thereby demonstrating a concentration-dependent antiviral effect (EC50 values ranging from 4.20 μM to 12.6 μM) and negligible cytotoxicity (CC50 > 50 μM) across diverse cell lines. Moreover, cell fluorescence staining and Western blotting assays revealed that dapoxetine effectively reduced the expression of ZIKV proteins. Collectively, our findings suggest that dapoxetine exhibits anti-ZIKV effects by inhibiting ZIKV RdRp activity, positioning it as a potential candidate for clinical therapeutic intervention against ZIKV infection.